Exploring Association of Level of Empathy with Demographic Factors among Medical and Dental Students, A Comparative Cross-Sectional Study: Level of Empathy among Medical and Dental Students - Aslam, Fatima; Noor, Sana; Malik, Aafia; Rameen, .; Javed, Gohar; Nasir, Hafsah; Ali, Anusha Nauroz; Nadeem, Mahnoor Sumaiya (Pakistan Journal of Health Sciences, 2024)
Being an effective physician, one must possess both clinical expertise and a specific range of emotional competencies, including empathy. Objective: To determine the empathy scores among medical and dental students and to correlate them with demographic factors like age, gender and academic year. Methods: A cross-sectional survey was conducted involving 324 students from medical and dental programs at a private medical and dental college in Lahore. Empathy levels were measured using Jefferson Scale of Physician Empathy- student version (JSPE-S). Data analysis was done using SPSS 24.0. Non-parametric tests were applied to find the significant difference between average scores of JSPE-S and all sub-scales across gender, age, academic year and medical program. Results: The mean empathy score on JSPE-S was 66.7. Difference of JSPE-S overall empathy score between age-groups was statistically significant (p-value 0.02). Among the medical and dental students significant difference was found between average scores of perceptive taking and compassionate care. No correlation was found between empathy scores and gender. However, empathy scores were low during initial years of medical school, being the highest in fourth year and then declining again. Conclusions: It was concluded that empathy is associated with demographical factors. Among the medical and dental students’ significant difference was found between average scores of perceptive taking and compassionate care. Although no difference in empathy scores was found between the two genders however, it declined as students gained more exposure to patients in their senior years